PENGARUH KUALITAS PENGELOLA KEUANGAN DAN SISTEM PENGENDALIAN INTERN PEMERINTAH (SPIP) TERHADAP EFEKTIVITAS PENGELOLAAN KEUANGAN DAERAH PADA INSPEKTORAT PEMERINTAH KOTA MANADO - Bulan, Sinambow Gloria Injilita; Tinangon, Jantje J.; Mawikere, Lidia (Universitas Sam Ratulangi, 2017)
The government's internal control system, in achieving the effectiveness of regional financial management, is required by the government apparatus (financial manager), and should be able to provide adequate assurance. This study aims to determine the effect of the quality of financial managers on the effectiveness of local financial management and the influence of internal control systems of government on the effectiveness of local financial management. This study uses the method of Pearson Correlation. In this study did not use the sample but took the population of all auditors including also functional apparatus as many as 45 people. Data were analyzed using multiple linear regression analysis with SPSS. The result of the research shows that there is a significant influence between the quality of financial manager and the government's internal control system on the effectiveness of local financial management.Keywords: quality of financial manager, internal government control system, effectiveness of regional financial management